Enhanced cortical activity of swallowing under acid stimulation in normal individuals: an fNIRS study - Gong, Shuang; Sun, WeiJun; Wu, LingLing; Kang, JiLiang; Tang, Min (Frontiers in Neurology, 2025)
IntroductionThe aims of this study are to investigate the activation patterns of the cerebral cortex in healthy individuals during liquid swallowing, as well as the differences in cerebral cortex activation between swallowing distilled water and swallowing acidic solutions, using functional near-infrared spectroscopy (fNIRS).MethodsEighteen healthy right-handed volunteers participated in this study. Each volunteer randomly completed two swallowing tasks: swallowing distilled water and swallowing an acidic solution, which differed in taste. By analyzing the average concentration of oxyhemoglobin across various channels, we observed the activation patterns and differences in brain regions when volunteers performed different swallowing tasks.ResultsDuring the act of swallowing distilled water, the significantly activated brain regions in the prefrontal cortex included the bilateral inferior frontal cortex and the right Broca’s area. When swallowing an acidic solution, the significantly activated regions in the prefrontal cortex were the bilateral inferior frontal cortex (IFC), bilateral orbitofrontal cortex (OFC), bilateral dorsolateral prefrontal cortex (DLPFC), right Broca’s area, left primary somatosensory cortex (S1), and left premotor/supplementary motor area (PMC/SMA). Paired t-tests revealed that the activation levels during the swallowing of acidic liquid were higher than those during the swallowing of distilled water in the bilateral dorsolateral prefrontal cortex, left primary somatosensory cortex, and left premotor/supplementary motor area.ConclusionFunctional near-infrared spectroscopy (fNIRS) can be applied to research on brain functions related to swallowing. It has revealed differences in the activation of brain regions between healthy individuals when swallowing distilled water and sour solutions. Swallowing sour liquids activates more brain areas compared to swallowing water, suggesting that sour stimuli effectively activate the swallowing cortical network.